Nuevas localidades para peces de agua dulce de la República Argentina, II - Miquelarena, Amalia María (1981)
Eight species of Characiformes (Aphyocharax alburnus, A. dentatus, Cheirodon leuciscus, C/i. piaba, Bryconame- ru us ihermgi, Cdandulocauda terojali, Hemiodus orthonops ami Leporinus striatus) and twc species of Siluriformes (Plat yd oras costatus and Bunocephalus coracoidem) are recorded from thirteen new Argentine localities. New distributional data are discussed. Relevant morphological measurements are added.